Implicit measure for yoga research: Yoga implicit association test - Judu V Ilavarasu; Sasidharan K Rajesh; Alex Hankey (International Journal of Yoga, 2014)
Context: The implicit association test (IAT), a new tool for yoga research is presented. Implicit measures could be used in those situations where (1) The construct is difficult to self-report, (2) there is a threat of social desirability. Clinically, we can assess cognitive dissonance by evaluating incongruence between implicit and explicit measures. Explicit preferences are self-reported. Implicit preferences are what we inherently believe, often without our conscious awareness. Aims: The primary objective of this study is to provide a bird′s eye view of the field, implicit cognition, with emphasis on the IAT and the secondary objective is to illustrate through an example of our study to develop an implicit tool to assess implicit preference toward yoga. Settings and Design: A total of 5 independent samples of total 69 students undergoing short and long-term yoga courses in a Yoga University were assessed for their implicit and explicit preferences towards yoga. Materials and Methods: The yoga-IAT (Y-IAT), explicit self-rating scale was administered through computers using the Inquisit program by Millisecond Software. Experimental and scoring materials are provided. Statistical Analysis Used: Data were extracted using recommended scoring algorithm and descriptive statistics highlighting basic psychometric properties of Y-IAT are presented along with its congruence with explicit self-measure. Results: A moderate preference toward yoga was detected, with a lower implicit-explicit congruence, reflecting possible confound of social desirability in the self-report of preference toward yoga. Conclusions: Implicit measures may be used in the yoga field to assess constructs, which are difficult to self-report or may have social desirability threat. Y-IAT may be used to evaluate implicit preference toward yoga.